2019
DOI: 10.3390/plants8090330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Markers Associated with Yield Traits and Morphological Features in Maize (Zea mays L.)

Abstract: Association mapping is a powerful approach to detect associations between traits of interest and genetic markers based on linkage disequilibrium in molecular plant breeding. The aim of this study was the identification of single nucleotide polymorphisms (SNPs) and SilicoDArT markers associated with yield traits and morphological features in maize. Plant material constituted inbred lines. The field experiment with inbred lines was established on 10 m2 plots in a set of complete random blocks in three replicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Extensive transcriptome profiling comparing inbred lines and their hybrids by means of DNA micro-array technology in maize [ 15 , 16 , 17 ] and allelic transcription variation due to cis -regulatory elements in maize [ 18 ] indicated that transcriptional regulation and transcriptional overdominance could play an important role as molecular mechanisms establishing hybrid vigor. Tomkowiak et al [ 19 ] examined inbred maize lines and consequently identified three SilicoDArT markers, 4591115, 7059939, and 5587991, related to the size of crop structure features. Tomkowiak et al [ 20 ] also tested SNP and SilicoDArT molecular markers on the same pool of plant materials in the context of selecting the parental components for heterosis crossing, and concluded that such markers could be useful in selecting plant material.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive transcriptome profiling comparing inbred lines and their hybrids by means of DNA micro-array technology in maize [ 15 , 16 , 17 ] and allelic transcription variation due to cis -regulatory elements in maize [ 18 ] indicated that transcriptional regulation and transcriptional overdominance could play an important role as molecular mechanisms establishing hybrid vigor. Tomkowiak et al [ 19 ] examined inbred maize lines and consequently identified three SilicoDArT markers, 4591115, 7059939, and 5587991, related to the size of crop structure features. Tomkowiak et al [ 20 ] also tested SNP and SilicoDArT molecular markers on the same pool of plant materials in the context of selecting the parental components for heterosis crossing, and concluded that such markers could be useful in selecting plant material.…”
Section: Introductionmentioning
confidence: 99%
“…It is an effective diagnostic technique for examining genetic diversity. The approach yields higher polymorphic markers, including codominant SNPs and dominant silicoDArT (Tomkowiak et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used for next-generation sequencing was described in detail in the publication presenting the research by Tomkowiak et al [ 53 ]. The DArTseq analysis was performed at Diversity Arrays Technology Pty Ltd. (Canberra, Australia).…”
Section: Methodsmentioning
confidence: 99%